Pengembangan Media Pop-Up Book bagi Pembelajaran Cerita Wayang Kelas IV Sekolah Dasar di Kabupaten Demak - Shinta Triwijaya; Suyitno Suyitno; Ari Widyaningrum (STKIP Andi Matappa Pangkep, 2022)
This study analyzes the feasibility of Pop Up Book teaching materials for Learning the Puppet story, material for Bima Bungkus, for Class IV students? The purpose of the study was to determine the feasibility of developing teaching materials using Pop Up Book media with Bima Bungkus story material to improve learning of wayang stories. This study uses the Research and Development method, the data analysis technique used is descriptive qualitative. The instrument is content validation assessment questionnaire, construct validation, initial field trials. Data collection was obtained from the results of content validation assessment, construct validation, initial field trials at SD Mranak 1 Demak. Based on the validation test and small-scale trial, Pop-Up Book media got a score from the material expert validation test of 83.2% and 93.7% and media expert validation test of 88%, a very decent category. This research on the development of Pop Up Book media received a teacher response for the learning design aspect of 85% and the communication aspect of 90%, a very feasible category. Pop Up Book media that has been developed is very valid and suitable to be used to improve learning ability of wayang stories for students in grade IV SD N Mranak 01 Demak.